Impact of Place Identity, Self-Efficacy and Anxiety State on the Relationship Between Coastal Flooding Risk Perception and the Willingness to Cope - Lemée, Colin; Fleury-Bahi, Ghozlane; Navarro, Oscar (Frontiers in Psychology, 2019)
This article investigates the predictors of coping willingness among citizens exposed to coastal flooding. We focus especially on how place identity, perceived self-efficacy, anxiety-state and coastal flooding risk perception shape both active and passive coping willingness. Data were obtained from different areas at risk of coastal flooding located in France. The sample is composed of 315 adult participants (mean age = 47; SD = 15). We observe a direct relation between risk perception and active coping willingness. The model did not confirm our expectations that a higher perceived self-efficacy would increase active coping willingness. Concerning passive coping strategies, the model reflects our expectations that a higher anxiety-state increases passive coping willingness, and that place identity acts as a mediator and reinforce the relation between anxiety-state and passive coping willingness. To our knowledge this is an unprecedented model that suggests the importance of anxiety-state and place identity in the study of coastal risks. Moreover, it suggests that place identity is reinforced when the living place is threatened and encourages the willingness to use passive coping strategies. Model fit indices suggest the good fit of our model and Bayesian model comparison reveals a very strong evidence of the better fit of this model compared to its saturated and independent equivalents.